APOBEC cellular enzymes as ‘court jesters’ in SARS-CoV-2 evolution - Philippe Colson; Pierre Pontarotti; Jacques Fantini; Anthony Levasseur; Christian Devaux; Didier Raoult (Virus Genes, 2026)

Characterization of human parainfluenza virus type 2 circulating in southern France between 2017 and 2022 using whole-genome sequencing - Enzo Bisi; Céline Boschi; Houmadi Hikmat; Jérémy Delerce; Lorlane Le Targa; Lucile Lesage; Aurélie Morand; Bernard La Scola; Philippe Colson (Virus Genes, 2026)

The disappearance of ORF8 in human-adapted coronaviruses: the Cheshire cat paradigm - Philippe Colson; Anthony Levasseur; Hervé Chaudet; Christian Devaux; Jacques Fantini; Pierre Pontarotti; Didier Raoult (Virus Genes, 2026)

Validation and redescription of Acanthamoeba terricola Pussard, 1964 (Amoebozoa: Acanthamoebidae) - Daniele Corsaro; Martin Mrva; Philippe Colson; Julia Walochnik (European Journal of Protistology, 2024)

Delineation of the adult phenotype of Coffin–Siris syndrome in 35 individuals - Ariane Schmetz; Hermann-Josef Lüdecke; Harald Surowy; Sugirtahn Sivalingam; Ange-Line Bruel; Roseline Caumes; Perrine Charles; Nicolas Chatron; Krystyna Chrzanowska; Marta Codina-Solà; Cindy Colson; Ivon Cuscó; et al. (Human Genetics, 2024)

Emergence in southern France of a new SARS-CoV-2 variant harbouring both N501Y and E484K substitutions in the spike protein - Philippe Colson; Jérémy Delerce; Emilie Burel; Jordan Dahan; Agnès Jouffret; Florence Fenollar; Nouara Yahi; Jacques Fantini; Bernard La Scola; Didier Raoult (Archives of Virology, 2022)
SARS-CoV-2 variants have become a major virological, epidemiological, and clinical concern, particularly with regard to the risk of escape from vaccine-induced immunity. Here, we describe the emergence of a new variant, with the index case returning from travel in Cameroon. For 13 SARS-CoV-2-positive patients living in the same geographical area of southeastern France, a qPCR test for screening variant-associated mutations showed an atypical combination. The genome sequences were obtained by next-generation sequencing with Oxford Nanopore Technologies on GridION instruments within about 8 h. Analysis revealed 46 nucleotide substitutions and 37 deletions, resulting in 30 amino acid substitutions and 12 deletions. Fourteen of the amino acid substitutions, including N501Y and E484K, and nine deletions are located in the spike protein. This genotype pattern led to the establishment of a new Pangolin lineage, named B.1.640.2, that is a phylogenetic sister group to the old B.1.640 lineage, which has now been renamed B.1.640.1. The lineages differ by 25 nucleotide substitutions and 33 deletions. The combination of mutations in these isolates and their phylogenetic position indicate, based on our previous definition, that they represent a new variant, which we have named “IHU”. These data are a further example of the unpredictability of the emergence of SARS-CoV-2 variants, and of their possible introduction into a given geographical area from abroad.

Occurrence of a substitution or deletion of SARS-CoV-2 spike amino acid 677 in various lineages in Marseille, France - Philippe Colson; Jeremy Delerce; Emilie Burel; Mamadou Beye; Pierre-Edouard Fournier; Anthony Levasseur; Jean-Christophe Lagier; Didier Raoult (Virus Genes, 2022)

Limited spread of a rare spike E484K-harboring SARS-CoV-2 in Marseille, France - Philippe Colson; Jacques Fantini; Nouara Yahi; Jeremy Delerce; Anthony Levasseur; Pierre-Edouard Fournier; Jean-Christophe Lagier; Didier Raoult; Bernard La Scola (Archives of Virology, 2022)

Direct next-generation sequencing diagnosis of echovirus 9 meningitis, France - Madjid Morsli; Jean-Jacques Vincent; Laurine Milliere; Philippe Colson; Michel Drancourt (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Automated Western immunoblotting detection of anti-SARS-CoV-2 serum antibodies - Sophie Edouard; Rita Jaafar; Nicolas Orain; Philippe Parola; Philippe Colson; Bernard La Scola; Pierre-Edouard Fournier; Didier Raoult; Michel Drancourt (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
ELISA and chemiluminescence serological assays for COVID-19 are currently incorporating only one or two SARS-CoV-2 antigens. We developed an automated Western immunoblotting as a complementary serologic assay for COVID-19. The Jess TM Simple Western system, an automated capillary-based assay, was used, incorporating an inactivated SARS-CoV-2 lineage 20a strain as the source of antigen, and total immunoglobulins (IgG, IgM, IgA) detection. In total, 602 sera were tested including 223 from RT-PCR-confirmed COVID-19 patients, 76 from patients diagnosed with seasonal HCoVs and 303 from coronavirus-negative control sera. We also compared this assay with the EUROIMMUN® SARS-CoV-2 IgG ELISA kit. Among 223 sera obtained from RT-PCR-confirmed COVID-19 patients, 180/223 (81%) exhibited reactivity against the nucleocapsid and 70/223 (31%) against the spike protein. Nucleocapsid reactivity was further detected in 9/76 (14%) samples collected from patients diagnosed with seasonal HCoVs and in 15/303 (5%) coronavirus-negative control samples. In the subset of sera collected more than 2 weeks after the onset of symptoms, the sensitivity was 94% and the specificity 93%, the latter value probably reflecting cross-reactivity of SARS-CoV-2 with other coronaviruses. The automated Western immunoblotting presented a substantial agreement (90%) with the compared ELISA (Cohen’s Kappa=0.64). Automated Western immunoblotting may be used as a second line test to monitor exposure of people to HCoVs including SARS-CoV-2.

Giant virus-related sequences in the 5300-year-old Ötzi mummy metagenome - Gabriel Augusto Pires de Souza; Clara Rolland; Bariaa Nafeh; Bernard La Scola; Philippe Colson (Virus Genes, 2021)

Children account for a small proportion of diagnoses of SARS-CoV-2 infection and do not exhibit greater viral loads than adults - Philippe Colson; Hervé Tissot-Dupont; Aurélie Morand; Céline Boschi; Laetitia Ninove; Vera Esteves-Vieira; Philippe Gautret; Philippe Brouqui; Philippe Parola; Jean-Christophe Lagier; Christine Zandotti; Matthieu Million; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ultrarapid diagnosis, microscope imaging, genome sequencing, and culture isolation of SARS-CoV-2 - Philippe Colson; Jean-Christophe Lagier; Jean-Pierre Baudoin; Jacques Bou Khalil; Bernard La Scola; Didier Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Viral RNA load as determined by cell culture as a management tool for discharge of SARS-CoV-2 patients from infectious disease wards - Bernard La Scola; Marion Le Bideau; Julien Andreani; Van Thuan Hoang; Clio Grimaldier; Philippe Colson; Philippe Gautret; Didier Raoult (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
In a preliminary clinical study, we observed that the combination of hydroxychloroquine and azithromycin was effective against SARS-CoV-2 by shortening the duration of viral load in Covid-19 patients. It is of paramount importance to define when a treated patient can be considered as no longer contagious. Correlation between successful isolation of virus in cell culture and Ct value of quantitative RT-PCR targeting E gene suggests that patients with Ct above 33–34 using our RT-PCR system are not contagious and thus can be discharged from hospital care or strict confinement for non-hospitalized patients.

Complete genome sequence of Tunisvirus, a new member of the proposed family Marseilleviridae - Sarah Aherfi; Mondher Boughalmi; Isabelle Pagnier; Ghislain Fournous; Bernard La Scola; Didier Raoult; Philippe Colson (Archives of Virology, 2014)

Complete genome sequence of Courdo11 virus, a member of the family Mimiviridae - Niyaz Yoosuf; Isabelle Pagnier; Ghislain Fournous; Catherine Robert; Bernard La Scola; Didier Raoult; Philippe Colson (Virus Genes, 2014)

Complete genome sequence of Cannes 8 virus, a new member of the proposed family “Marseilleviridae” - Sarah Aherfi; Isabelle Pagnier; Ghislain Fournous; Didier Raoult; Bernard La Scola; Philippe Colson (Virus Genes, 2013)

“Megavirales”, a proposed new order for eukaryotic nucleocytoplasmic large DNA viruses - Philippe Colson; Xavier De Lamballerie; Natalya Yutin; Sassan Asgari; Yves Bigot; Dennis K. Bideshi; Xiao-Wen Cheng; Brian A. Federici; James L. Van Etten; Eugene V. Koonin; Bernard La Scola; Didier Raoult (Archives of Virology, 2013)

High‐throughput isolation of giant viruses of the M imiviridae and M arseilleviridae families in the T unisian environment - Mondher Boughalmi; Hanene Saadi; Isabelle Pagnier; Philippe Colson; Ghislain Fournous; Didier Raoult; Bernard La Scola (Environmental Microbiology, 2013)
Summary Giant viruses of the M egavirales order have been recently isolated from aquatic environments and have long been neglected because they are removed from samples during viral purification for viral metagenomic studies. Due to bacterial overgrowth and susceptibility to high concentrations of antibiotics, isolation by amoeba co‐culture has a low efficiency and is highly time‐consuming. Thus, few environments have been exhaustively investigated to date, although the ubiquitous distribution of the A canthamoeba sp. suggests that these viruses could also be ubiquitous. In this work, we have implemented a high‐throughput method to detect amoebae lysis on agar plates that allows the testing of hundreds of samples in a few days. Using this procedure, a total of 11 new M arseilleviridae strains and four new M imiviridae strains, including a virus infected with a virophage, were isolated from 1000 environmental samples from T unisia. Of these, four corresponded to new genotypic variants. These isolates are the first A frican environmental isolates identified from these two families, and several samples were obtained from a hypersaline aquatic environment. These results demonstrate that this technique can be used for the evaluation and characterization of large collections of giant viruses to provide insight into understanding their ecology.

“Marseilleviridae”, a new family of giant viruses infecting amoebae - Philippe Colson; Isabelle Pagnier; Niyaz Yoosuf; Ghislain Fournous; Bernard La Scola; Didier Raoult (Archives of Virology, 2013)